P113 Home delivery influences medicines possession ratio in adult cystic fibrosis. (December 2018) - Dooney, MK; Martin, KJ; Iqbal, N; Jones, AM; Barry, PJ
Abstract : Objectives: Medication adherence remains a significant challenge in adult cystic fibrosis. Nebulised therapies are amongst the most burdensome for patients. Medicines possession ratio (MPR) is a calculable surrogate for adherence using data from hospital records and pharmacy deliveries. In our centre, we recently adopted a homecare delivery method for nebulised therapies. We aimed to examine whether this potentially more convenient method of medication distribution would affect MPR. Method: All patients who were prescribed a nebulised mucolytic or antibiotic and had the delivery method changed to homecare in 2016 were included in the sample population. Prescriptions were excluded if the medication was a new prescription, medication was changed or stopped. MPR was calculated by standard methodology and capped at 100%. Data was tested for normality and appropriate statistical testing was used. Results: We screened 72 prescriptions of nebulised drugs delivered by homecare. Valid data was available for 50 prescriptions in 44 patients. Prescriptions had been valid for a median of 288 [185 – 345] days prior to delivery method change and 324 [237 – 381] days after. MPR significantly increased with homecare delivery method from a median of 67.9% [48.1–92.4] to 79.9% [60.7–98.0], p=0.003. Conclusion: Medicines possession ratio is influenced by the method of obtaining medication. Delivering medication directly to patients' homes or places of work rather than using standard collection increased MPR significantly. This suggests that making medication more readily and conveniently available may influence medication adherence. These patients need to be followed longitudinally to assess whether these changes impacted on clinical outcomes.